Research on Detection Technology of Joint Sealing of Large Diameter PVC Water Supply Pipe. Issue 2 (April 2021) - Meng, Fanzhao; Yang, Ruiqing; Yang, Yonghai; Wei, Daifeng
Abstract: With the increasing application of PVC water supply pipe in production and life, this paper aims at the problem that there is no single sealing ring connected large diameter PVC pipe interface sealing detection equipment in the construction site of agricultural water supply. According to the sealing test method of negative pressure test, a set of large diameter PVC pipe interface sealing test device is designed, and the corresponding test procedures and standards are put forward. The field sealing test of large diameter PVC pipe interface is carried out, and the portable aviation aluminum box with universal wheel is designed and customized. The device has the advantages of simple structure, easy installation and disassembly, easy carrying, and is suitable for field operation. It provides important equipment support for the better promotion and use of large PVC pipes.